Tecnologia alternativa para tratamento de efluente proveniente de frigorífico de peixes - Sone, Ana Paula (2013)
The growing demand for white meat prompted the expansion of fish slaughterhouses activities, but this growth has brought with it the generation of large amounts of waste, which, if left untreated become serious environmental problems. In this context, the present study aimed to develop an alternative technology for wastewater treatment from fish slaughterhouses. The methodology included the realization of 5 steps: 1) to characterize the source of waste; 2) the qualitative and quantitative characterization of the slaughterhouse waste; 3) study to assess the performance of methods, processes and conventional technologies; 4) the development / construction of an alternative technology for slaughterhouses wastewater treatment; 5) experimental tests of alternative technology and reviewing the performance of the technology developed. The results include a breakdown of the production process (flowchart), a correlation (quantitative relationship between raw material, product and waste) that allows the total estimate (0.635 tonne of solid waste per tonne of processed fish and 12.5 m3 of effluent per tonne of processed fish) and partial (33% carcass, 20% head, 11% leather with scales, 6% gills, 5% gut, 5% burrs fillet, 4% liver, 4% spiny dorsal fin, 3% operculum, 3% caudal fin, 1% pelvic fins, 1% pectoral fins, 1% eye and 1% anal fin) generation by mass of fish waste from slaughterhouses, analysis of effluent (the refrigerator under study) and, development / construction of alternative technology.